2002
DOI: 10.1086/340501
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Responses to Lipo‐oligosaccharide ofNeisseria meningitidisImmunotype Strains in Relation to Virulence and Disease

Abstract: Inflammatory responses to lipo-oligosaccharide (LOS) contribute to the severity of meningococcal disease. Strains that express the L(3,7,9) LOS immunotypes are isolated from the majority of patients, but other immunotypes are isolated predominantly from carriers. Inflammatory responses elicited from a human monocytic cell line (THP-1) that had been pretreated with vitamin D3 (VD3) were compared after stimulation with purified LOSs from standard immunotype strains. The neutralizing effects of normal human serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
2
27
0
2
Order By: Relevance
“…Our previous work and that of others has shown that the LA portion of Neisserial LOS is the bioactive component (6,(10)(11)(12)(13). Several studies have shown with the use of mutational or enzymatic alterations of LOS that structural modifications of Neisserial LA result in substantial differences in biological potency (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our previous work and that of others has shown that the LA portion of Neisserial LOS is the bioactive component (6,(10)(11)(12)(13). Several studies have shown with the use of mutational or enzymatic alterations of LOS that structural modifications of Neisserial LA result in substantial differences in biological potency (11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 94%
“…There have been several reported mutational or enzymatic alterations of the acylation pattern of the Neisserial LA leading to modulation of its endotoxic activity as measured by various assays (11)(12)(13). Inactivation of genes lpxL1 or lpxL2 involved in acylation of the LA resulted in a lipid, which was pentaacylated or tetraacylated, respectively, rather than hexaacylated, and in both cases the LOS induced less TNF-a from a human macrophage cell line (13).…”
mentioning
confidence: 99%
“…It is therefore likely that the variation we see in the TNF response of THP-1 cells and in TLR4/MD2 signaling induced by LOS from different Neisseria strains is due to differences in the lipid A portion of the molecule. There have been many reported alterations of lipid A structure leading to modulation of its endotoxic activity as measured by various assays (4,9,43,49). It has been shown that the acylation pattern of lipid A is an important determinant of endotoxin activity.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-incubation with VitD3 did not affect either the type or quantity of cytokines tested, but this step was retained in our studies. In contrast to endotoxin, 25 expression of the CD14 antigen does not appear to affect responses of THP-1 cells to A. otitidis or S. pneumoniae.…”
Section: Cytokines Stimulated By a Otitidismentioning
confidence: 78%
“…To induce expression of CD14, THP-1 cells (2.5 Â 10 5 cells/ml) were pretreated with 10 À7 M VitD3 for 72 h prior to use in stimulation assays. 25 CD14 expression of VitD3-differentiated THP-1 cells was confirmed by flow cytometry (Hunter Area Pathology Service, Newcastle, Australia).…”
Section: Materials and Reagentsmentioning
confidence: 98%